2004
DOI: 10.1172/jci200421146
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of Nrf2 enhances susceptibility to cigarette smoke–induced emphysema in mice

Abstract: Although inflammation and protease/antiprotease imbalance have been postulated to be critical in cigarette smoke-induced (CS-induced) emphysema, oxidative stress has been suspected to play an important role in chronic obstructive pulmonary diseases. Susceptibility of the lung to oxidative injury, such as that originating from inhalation of CS, depends largely on its upregulation of antioxidant systems. Nuclear factor, erythroid-derived 2, like 2 (Nrf2) is a redox-sensitive basic leucine zipper protein transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
464
4
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 803 publications
(490 citation statements)
references
References 36 publications
20
464
4
2
Order By: Relevance
“…Under normal conditions, nuclear levels of Nrf2 are low; however, under stress such as oxidative stimuli, nuclear accumulation of Nrf2 increases, resulting in enhanced transcriptional activation of its targets, which in turn confers protection against various environmental stresses (7)(8)(9)(10)(11)(12). Here, we report that Nrf2 is a novel regulator of the innate immune response that dramatically improves survival during experimental sepsis by protecting against dysregulated inflammation.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Under normal conditions, nuclear levels of Nrf2 are low; however, under stress such as oxidative stimuli, nuclear accumulation of Nrf2 increases, resulting in enhanced transcriptional activation of its targets, which in turn confers protection against various environmental stresses (7)(8)(9)(10)(11)(12). Here, we report that Nrf2 is a novel regulator of the innate immune response that dramatically improves survival during experimental sepsis by protecting against dysregulated inflammation.…”
Section: Introductionmentioning
confidence: 83%
“…Nuclear proteins were isolated from tissue or cells by using the protocol described previously (7). The NF-kB probe (5′-GTTGAGGGGACTTTCCCAGGC-3′) (Promega) was end-labeled by T4 polynucleotide kinase in the presence of [ 32 P] ATP g. For EMSA, 5 mg of nuclear proteins was incubated with the labeled NF-kB probe in the presence of poly(dI-dC) in binding buffer (Promega) at 4°C for 20 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, researchers have found that disruption of the Nrf2 gene, a transcriptional regulator of antioxidant enzymes, led to accelerated and more extensive cigarette smoke-induced emphysema in mice (12,47). Furthermore, elastase-provoked emphysema was markedly exacerbated in Nrf2-deficient mice compared with WT mice (48).…”
Section: Discussionmentioning
confidence: 99%
“…These trends indicate that the development of pulmonary emphysema is affected by other important factors. Several candidate genes have been implicated in determining susceptibility to pulmonary emphysema: α-1 antitrypsin (α1-AT) (7), macrophage elastase (8), klotho (9), surfactant D (10), microsomal epoxide hydrolase (11), and nuclear factor erythroid 2-related factor 2 (Nrf2) (12). Alterations in these genes have been shown to lead to oxidant/antioxidant or protease/antiprotease imbalances, which are pivotal to the pathogenesis of emphysema (4).…”
Section: Introductionmentioning
confidence: 99%